Simultaneous pectus excavatum correction and lung transplantation–A case series. Issue 1 (4th August 2020) - Rahimi, Nina; Matilla, Jose R.; Lang, György; Schwarz, Stefan; Nachbaur, Edith; Benazzo, Alberto; Klepetko, Walter; Jaksch, Peter; Hoetzenecker, Konrad
Abstract : Severe chest wall deformities are considered an absolute contraindication for lung transplantation. The significantly impaired chest compliance associated with pectus excavatum is thought to result in a high risk of postoperative respiratory complications and significant morbidity and mortality. We herein report our pooled institutional experience consisting of 3 patients who underwent bilateral lung transplantation and simultaneous correction of a pectus excavatum. Two of the patients were children and 1 patient had severe asymmetric pectus. All patients received a size‐reduced double lung transplant and the deformity was corrected by a Nuss or modified Ravitch procedure. The perioperative course was complicated by prolonged weaning requiring tracheostomy in 2 of the 3 patients. However, long‐term results were good and all 3 patients are alive in excellent clinical condition 72, 60, and 12 months after the transplantation. This case series demonstrates that patients with severe chest wall deformities should not a priori be excluded from lung transplantation, and a combined approach is feasible for selected patients. Abstract : This case series suggests that, for selected cases, lung transplantation with simultaneous correction of severe chest wall deformity may be feasible.